Florística de uma reserva particular do patrimônio natural em fragmento de Mata Atlântica (Itaara, RS, Brasil) - Ferrarese, Marina Deon (2016)
There are two biomes in the state of Rio Grande do Sul - the Atlantic Forest and the Pampa. According to official agencies, they represent the smallest native vegetation coverages left in Brazil, and only about 2.6% of this territory is protected in Conservation Units (CUs).Thus, we see the importance of the implementation of CUs in these areas of the state, as well as the need for knowledge of the flora, in order to provide effective measures to preserve not only species, but of the whole ecosystem. This study aimed to carry out the floristic survey (native vascular plants) of a fragment located in a biome area of Atlantic Forest, in the forest edge of the Serra Geral, in the MO Ã Private Reserve of the State Natural Heritage, located in the municipality of Itaara, Rio Grande do Sul, Brazil.To do so, in the period between 2014 and 2015, fifteen collecting expeditions took place in the study area, by the Caminhamento method, covering the sixteen seasons. The collected material was identified, herborized and forwarded for inclusion in the SMDB herbarium. In total, there were 277 native taxa from Brazil, belonging to 72 families. Among the Angiosperms, the highest number of species was distributed in the Asteraceae, Poaceae and Fabaceae families; among the Ferns, the highest number was from the Polypodiaceae, Pteridaceae and Dryopteridaceae families. The group of Gymnosperms was represented by the Araucaria angustifolia (Bertol.)Kuntze and Podocarpus lambertii Klotzsch ex Endl. This study provided a table including the families and species with their habit, illustrations, and information on the occurrence of species in the different environments of the area that was studied, as well as their degree of threat in Rio Grande do Sul. The results extend the knowledge of the local flora and of the edge Plateau of Rio Grande do Sul in Itaara, also demonstrating the importance and potential of the studied site.